Vaginal Injury Due to Inflicted Self-Medication: A Rising Concern - Md Zin, Hezlin; Hashim , Hazwani Hanum; Draman , Samsul (IIUM Medical Journal Malaysia, 2022)
Improper self-treatment of vaginal discharge may result in various complications to the patient. We reported a case of a 24-year-old single and nulliparous lady with an oak gall stick lodged in her vagina during an attempt to treat her own vaginal discharge. During an examination under anaesthesia (EUA), her hymen was noted to be torn and a foreign body was identified and removed out from her vaginal. Her upper vaginal swab cultures negative for any pathogen. We concluded that this was a case of intravaginal foreign body complicated with vaginal injury secondary to a self-medication for vaginal discharge by using a herbal stick. Hence, the public should be educated to seek proper medical treatment rather than performing self-treatment.